Analysis Of Cabbage Farming Production And Income In Selupu Rejang District, Rejang Lebong Regency - Anggel Almunawar; Bambang Sumantri; Ellys Yuliarti; Alfayanti Alfayanti (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: This study aims to analyze various factors influencing cabbage farm production and to assess the income generated from cabbage farming. Methodology: The research was conducted in Selupu Rejang Subdistrict, Rejang Lebong Regency, using both primary and secondary data as sources of information. The sample was selected using purposive sampling, resulting in 92 cabbage farmers from the four largest cabbage-producing villages in Selupu Rejang Subdistrict, namely Sambirejo, Sumber Bening, Karang Jaya, and Sumber Urip. The data analysis methods employed were the Cobb-Douglass production function analysis and income analysis. Results: The study found that land area, manure, Gracia pesticide, Seprint pesticide, male family labor (TKDK), and female family labor (TKLK) had a statistically significant effect on cabbage production in Selupu Rejang Subdistrict. The average income from cabbage farming was IDR 7,166,834 per farming unit per planting season (Ut/Mt), equivalent to IDR 27,821,659 per hectare per planting season (Ha/Mt). Findings: This income level indicates that cabbage farming in Selupu Rejang Subdistrict provides a reasonable profit for farmers. Originality: This study highlights the factors influencing cabbage farm production and income. Novelty: The study offers an in-depth analysis of both the production and financial aspects of cabbage farming. Conclusion: Cabbage farming in Selupu Rejang Subdistrict is profitable and feasible to pursue.